THE USE OF CHATGPT AS A SELF-LEARNING TOOL FOR ENGLISH LANGUAGE LEARNING AMONG UNIVERSITY STUDENTS - Milatus Sa'adah; Zainuddin Zainuddin; Beny Hamdani (Universitas Wiralodra, 2025)
The application of language model based on artificial intelligence, like a ChatGPT, as a self-learning tool is one of the most recent innovations garnering attention in the rapidly evolving field of technology-assisted English language learning. The objective of the study on the application of ChatGPT as a self-directed learning resource for university students studying the English language encompasses: evaluating the effectiveness of ChatGPT in improving English language skill, assessing its impact in accelerating material comprehension, identifying challenges faced by students, and analyzing their motivations and experiences. Conducted as a qualitative research using thematic analysis. Data collection involved steps of data coding, theme categorization, and interpretation of result that describe students experience and views. In conclusion, university students can benefit greatly from using ChatGPT as a self-learning tool for English language acquisition.